2020
DOI: 10.1039/d0ob01447h
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the conformational behavior of cyclic octadepsipeptides with their ionophoric property and membrane permeability

Abstract: Cyclic octadepsipeptides such as PF1022A and its synthetic derivative emodepside exhibit anthelmintic activity with the latter sold as a commercial drug treatment against gastrointestinal nematodes for animal health use. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 83 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…Due to the high lipophilicity of the depsipeptides, incorporation into the membrane was hypothesized as a potential explanation for the apparent low permeability [ 15 ]. However, both cyclosporin A and emodepside are highly permeable in Caco-2 and MDCK-MDR1 cells, although they are only slightly less lipophilic compared with the other four depsipeptides ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the high lipophilicity of the depsipeptides, incorporation into the membrane was hypothesized as a potential explanation for the apparent low permeability [ 15 ]. However, both cyclosporin A and emodepside are highly permeable in Caco-2 and MDCK-MDR1 cells, although they are only slightly less lipophilic compared with the other four depsipeptides ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to its poor in vitro permeability as reported in [15], emodepside is highly permeable in standard cellular permeability assays (Table 2). Surprisingly, for all four BI depsipeptides derived from modifications of the side-chains of emodepside, no meaningful permeability data could be obtained in MDCK-MDR1 and Caco-2 cells.…”
Section: In Vitro Permeability and Efflux Measured For Depsipeptides In Standard Assaysmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent study demonstrated modulation of scaffold rigidity to engineer favorable ADME properties in macrocyclic peptides (Furukawa et al, 2020). Finally, drug design strategies, such as N-methylation or replacing NH with sulfur (or vice versa), were found to improve pharmacological activity, solubility, and/or permeability of macrocycles (Mallinson and Collins, 2012;Liras and McClure, 2019;Stadelmann et al, 2020;Buckton et al, 2021). Extending studies of this nature to macrocyclic hybrids is expected to improve their oral bioavailability for systemic uses.…”
Section: Limitations and Ways Forward In Macrocycle-antibiotic Hybrid Approachmentioning
confidence: 99%